Tranylcypromine Cephalgia - Mann, Alan M. (1963)
Tranylcypromine, a useful antidepressant agent, has been linked with a clinical syndrome of undetermined incidence characterized by exceedingly severe and prolonged headache. Associated phenomena may include paroxysmal hypertension, pallor, chest pain and collapse. This violent reaction does not seem to be related to age, sex, duration of treatment, or pre-existing cardiovascular disease; nor is it possible to predict in whom it will occur. The clinical picture may sometimes be quite similar to that produced by subarachnoid hemorrhage or by pheochromocytoma. The mechanism of action is not known, although it is possible that the syndrome may be due to an amphetamine-like effect; i.e., that tranylcypromine influences the adrenergic component of the reticular activating system. The occurrence of severe headache in the course of tranylcypromine therapy is an indication for immediate withdrawal of the drug. Tranylcypromine cephalgia should be considered as part of the differential diagnosis of sudden, violent and prostrating headache.